Assessing the Efficiency of Plastic Waste Management at Universitas Gadjah Mada Academic Hospital - Anindya Monika Putri; Rifdah Wardani; Dewi Saptowati (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Plastic waste from infusion bottles and hemodialysis solution containers constitutes a major component of hospital-generated hazardous waste (B3). Effective management of this material is essential to reduce environmental impact and promote sustainable hospital practices. The Universitas Gadjah Mada Academic Hospital (RSA UGM) has implemented a systematic approach to optimize its handling and utilization. Objective : This study aims to evaluate the utilization and effectiveness of managing infusion bottle waste and used hemodialysis solution containers at RSA UGM in terms of cost efficiency and microbial reduction. Research Methods/ Implementation Methods : This descriptive observational study applied a cross- sectional design. Primary data were obtained through observation and in-depth interviews, while secondary data were collected from hospital documents. Data collection was conducted between September and November 2021. The analysis focused on process efficiency, cost-effectiveness, and microbiological safety. Results : From January 2020 to October 2021, RSA UGM produced 16,467.17 kg of infusion and hemodialysis plastic waste, consisting of 76% infusion bottles and 24% jerrycans. The management process involved segregation, washing, chlorine disinfection, shredding, and licensed disposal. Microbial analysis indicated a substantial decrease in contamination levels—from 1.2×104 cfu/g before to 2.2×102 cfu/g after decontamination. Conclusion/Lesson Learned : The waste management system implemented at RSA UGM demonstrated microbiological effectiveness, indicating that structured handling and recycling of medical plastic waste can significantly support environmentally sustainable healthcare operations.